2016
DOI: 10.1590/0004-282x20160091
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ satisfaction with and views about treatment with disease-modifying drugs in multiple sclerosis

Abstract: Objective The treatment of multiple sclerosis (MS) with disease-modifying-drugs (DMDs) is evolving and new drugs are reaching the market. Efficacy and safety aspects of the drugs are crucial, but the patients’ satisfaction with the treatment must be taken into consideration. Methods Individual interview with patients with MS regarding their satisfaction and points of view on the treatment with DMDs. Results One hundred and twenty eight patients attending specialized MS Units in five different cities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
3
1
3
Order By: Relevance
“…The present study showed that half of the patients were satisfied or very satisfied with their treatment, whereas other authors 27 have indicated that over 80% of patients perceived treatment as beneficial. A study by Glanz et al 28 showed that for injections of interferon beta-1a administered subcutaneously, convenience and overall satisfaction with treatment were associated with decreased adherence.…”
Section: Discussioncontrasting
confidence: 74%
“…The present study showed that half of the patients were satisfied or very satisfied with their treatment, whereas other authors 27 have indicated that over 80% of patients perceived treatment as beneficial. A study by Glanz et al 28 showed that for injections of interferon beta-1a administered subcutaneously, convenience and overall satisfaction with treatment were associated with decreased adherence.…”
Section: Discussioncontrasting
confidence: 74%
“…Responses were scored from 1 to 5 on a Likert scale, where (1) indicates "I do not agree at all," (2) indicates "I tend to disagree," (3) indicates "I have no opinion," (4) indicates "I tend to agree," and (5) indicates "I totally agree." Questions comprise four aspects representing the personal impressions of treatment benefit, tolerability, convenience of use, and general satisfaction with the treatment [2].…”
Section: Methodsmentioning
confidence: 99%
“…Box 641, Riyadh, Saudi Arabia. 2 Armed Forces Hospitals Southern Region Saudi Arabia, Khamis Mushayt, Saudi Arabia. 3 King Abdulaziz Medical City, NGHA, Riyadh, Saudi Arabia.…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…No Brasil, a prevalência varia de acordo com a região geográfica, encontra-se uma maior incidência da doença, nas regiões Sul e Sudeste, porém devido à mistura de raças com influência Europeia gerou um aumento nos estados de São Paulo e Minas Gerais. Estudos definem que são as características genéticas que definem a maior ou menor frequência da EM entre os indivíduos e não o local onde residem (BRUM et al, 2014;FRAGOZO, 2014;SPESSOTO et al, 2016;FERNANDES et al, 2013).…”
Section: Esclerose Múltiplaunclassified